Hypothetical Model of Indonesian Coffee Community Cooperative (Koperasi Komunitas Kopi Indonesia, KOKOPI) in the Framework of Community Development and Interaction Design Through Kopikita App - Fadilla, Atria Nuraini; Indriati, Lisa; Aditia, Patra (Universitas Negeri Semarang, 2023)
The world of coffee in Indonesia is entering its third wave, marked by the tendency for coffee drinkers to know more about the journey of coffee from being harvested to serving. This research aims to formulate a hypothetical model for the development of the Indonesian Coffee Community Cooperative (KOKOPI) within the framework of community development theory. In its activities, KOKOPI, as a community representation that marks the third wave in the development of the phenomenon of coffee-drinking culture in Indonesia, has implemented the seven elements of the community development theory. However, it is not very concrete in one element regarding the integration of these disparate concerns and paradoxes within the field. This research offers a proposal for digital platform based through the Kopikita App as an effort to improve and complete the elements that have not been concretely implemented. Using an interaction design approach, the Kopikita App is expected to encourage the development of the KOKOPI community so that it can facilitate the coffee ecosystem chain more thoroughly.